S165. GLUTAMATERGIC ABNORMALITIES IN EARLY SCHIZOPHRENIA AND BIPOLAR DISORDER MEASURED USING WHOLE-BRAIN SPECTROSCOPY - Lenroot, Rhoshel; Upston, Joel; Mayer, Grace; Jones, Thomas; Maudsley, Andrew; Gasparovic, Charles; Tohen, Mauricio; Bustillo, Juan (Schizophrenia bulletin, 2020)
BackgroundGlutamatergic abnormalities in schizophrenia and bipolar disorder gave been identified using proton magnetic resonance spectroscopy (1H-MRS). Although schizophrenia and bipolar disorder are both known to involve extensive brain networks, most MRS studies have been done using single-voxel techniques. In this study we used whole brain 1H-MRS to examine glutamine-plus-glutamate (Glx) in early schizophrenia and bipolar disorder to examine metabolic abnormalities associated with affective and non-affective psychosis and with exposure to antipsychotic medication.MethodsThree dimensional 1H-MRS was acquired in young schizophrenia (SCZ, N=36, 24 M, 22.8±3.9 years, 19 antipsychotic-naïve and 17 antipsychotic-treated), bipolar (N=13, 5 antipsychotic-naïve and 8 antipsychotic-treated), schizoaffective-bipolar type (N= 3, 2 antipsychotic-naïve and 1 antipsychotic-treated) subjects, and healthy controls (HC, N=29, 17M, 23±4.4yrs). Glx, N-acetylaspartate, choline, myo-inositol and creatine group contrasts from all individual voxels that met spectral quality were analyzed in common brain space (voxel-wise p-threshold=0.001), followed by cluster-corrected alpha value (p<0.05). Bipolar subjects (N=13) and schizoaffective-bipolar type (N=3) were combined (SBP) (N=16, 11M, 21.9±2.9yrs, 7 antipsychotic naïve and 9 antipsychotic-treated).ResultsSCZ subjects compared to HC had lower Glx in the left superior (STG) and middle temporal gyri (16 voxels, p=0.04) and increased creatine in two clusters involving left temporal, parietal and occipital regions (32, and 18 voxels, p=0.02 and 0.04, respectively). Antipsychotic-treated and naïve SCZ had similar Glx reductions (8/16 vs 10/16 voxels respectively, but p’s>0.05). However, creatine was higher in antipsychotic-treated vs HC’s in a larger left hemisphere cluster (100 voxels, p=0.01). Also in treated SCZ, choline was increased in left middle frontal gyrus (18 voxels, p=0.04). Finally, in antipsychotic-naive SCZ, NAA was reduced in right frontal gyri (19 voxels, p=0.05) and myo-inositol was reduced in the left cerebellum (34 voxels, p=0.02). SBP subjects had no significant differences from HC in any area of the brain for any of the metabolites at a voxel-wise p-threshold of 0.001. A cluster of reduced Glx was found at in the right cuneus and precuneus (276 voxels, p=0.05) using a less stringent voxel-wise p-threshold of p< 0.05.DiscussionData-driven spectroscopic brain examination supports the presence of reductions in Glx in the left STG early in the course of schizophrenia; this was not seen in individuals with bipolar symptoms. A trend toward decreased Glx in the right cuneus and pre-cuneus in bipolar and schizoaffective patients is consistent with previous findings of abnormal function in this area. The left STG may be a critical target for postmortem and neuromodulation studies in schizophrenia studies.